The handbook of business and corruption : cross-sectoral experiences - Assländer, Michael S.; Hudson, Sarah, 1964- (Emerald handbooks in business and management., 2017)
The Handbook of Business and Corruption provides an overview of corrupt business practices in general and, more particularly, in different industry sectors, considering such practices from an ethical perspective.